INDUSTRI HOLLYWOOD SEBAGAI LEGITIMASI KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DI TIMUR TENGAH TAHUN 2013-2018 - Muhammad Daris Tantowi Ikram; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to show the problems that occur in the Middle East and the humanitarian conflicts that occur there. Conflicts which occur, rather than to be resolved, but it is even more complex because of the presence of countries that have great interests there, thus making the situation worse that conflict often ends in war. The United States is one of the countries that has a big interest in the Middle East, as evidenced by the US foreign policy agendas putting the Middle East in primary positions. This research theoretically has built using the perspective of constructivism on International Relations and supported by public diplomacy theory. Formulation of all arguments, data, facts, and theoretical frameworks in this study using the method of qualitative explanation. This research also use agent and structure as a level of analysis. This study aims to describe the condition of the legitimacy of US Foreign Policy in the Middle East which is considered as something that is true through the fastener of the Hollywood Industry as the only film industry that dominates the world. The policies of the United States in the Middle East in the name of democracy are actually injuring the meaning of democracy itself. Through the Hollywood industry, America did propaganda to be considered as something that was permissible.Keywords : Hollywood, US Foreign Policy, Legitimate, Propaganda